Evidence mapping of interactions on concomitant use of Chinese medicine and platinum-based chemotherapy: a scoping review protocol - Ai Ch’i Liew; Si Yan Chan; Ren Jye Lim; Wan Najbah Nik Nabil; Shi Min Hoo; Nai Ming Lai (Integrative Medicine Research, 2020)
Background: The utilization of Chinese herbal medicine (CHM) has gained popularity and acceptance worldwide. Increasing use of CHM either as a stand-alone or an adjunctive treatment for cancers has given rise to increasing concern on potential herbal-drug reactions. Possible combinatory effects are important to be explored in evaluating the rationality of integrating CHM and chemotherapy in clinical practice. This study aims to update the current knowledge on herbal-drug interactions (HDI) of the commonly used platinum-based chemotherapy (PtC) in cancer patients. Methods: Systemic searches will perform on online databases (English and Chinese) to identify papers from inception until December 2019 for inclusion into the review. The search strategy will be following PRISMA Scoping Reviews Checklist as a quality assurance step. All records retrieved will be screened by 2 independent reviewers. The preclinical studies and clinical studies that involve in assessing the concurrent use of CHM and PtC will be considered. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses will be used as scoping review framework. Discussion: This scoping review will explore the compatibility or combination rule of CHM-PtC and assist in understanding HDI in CHM-PtC co-treatment. Identification of active properties in CHM’s HDI and understanding pharmacokinetics and pharmacodynamic of the CHM alone or as co-treatment are essential for patients’ safety profile. It will provide a new insight for future practice in cancer treatment. Study registration: This protocol has been registered in the Research Register (https://www.researchregistry.com/) with an unique registration number: reviewregistry790.